PKM: Penyusunan Paket Wisata Lintas Desa Dalam Mewujudkan Desa Wisata Kerambitan Terintegrasi - I GD Yudha Partama; I Dewa Gede Agung Pandawana; Dewa Gede Agung Gana Kumara; Ni Made Dwi Puspitawati; Anak Agung Ayu Dian Andriyani; I Made Wahyu Wijaya (LPPM STIKOM Tunas Bangsa, 2022)
Tourism Awareness Groups (Pokdarwis) have been established in each and every village in the Kerambitan District as part of the government's ongoing effort to promote village tourism. The economic potential of the village's natural resources is underutilized because the Pokdarwis party does a poor job of managing and capitalizing on tourism opportunities to tap into these resources. Each of the Kerambitan District's villages features a Tourist Destination of Interest (DTW), which represents a golden opportunity to earn from tourism by creating and selling a customized tour package. Kerambitan District's DTW is mostly made up of natural tourism possibilities, such as rice fields and beaches. Kerambitan District's attractions rely only on entrance fees from tourists for revenue, hence there are no tour packages available at this time. The objective is that this package would encourage more people to visit Kerambitan District and enjoy its many attractions. SIGADis, a web-based tool, is used to aid partners in the Kerambitan District with promotions, reservations, and ticket sales. To develop an integrated system in the Kerambitan District, this SIGADis app provides details on DTW in the form of narratives and visuals, as well as tour packages, ancillary services, lodging options, and geographic coordinates. Partners receive support and training as they learn to use the SIGADis application. The effectiveness of the SIGADis application training was evaluated by administering surveys to course participants, with scores averaging between 80% and 90%. These results indicate that individuals now comprehend how to utilize the SIGADis application better than previously